2014
DOI: 10.2503/jjshs1.ch-099
|View full text |Cite
|
Sign up to set email alerts
|

Two Novel Self-compatible S Haplotypes in Peach (Prunus persica)

Abstract: Peach (Prunus persica) as a species is self-compatible (SC), although most other Prunus fruit tree species are partially or fully self-incompatible. We previously identified 3 mutated S haplotypes, S 1 , S 2 , and S 2m, that confer self-compatibility on commercial peach cultivars for fruit production. In this report, we identified 2 novel SC S haplotypes, S 3 and S 4 , among 130 peach cultivars and strains consisting mainly of ornamental cultivars and wild strains. The S 3 haplotype was found only in ornamenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 16 publications
3
12
1
Order By: Relevance
“…As a result, two out of the four DNA fragments were identical to S 1 -and S 2 -RNase alleles. The remaining two DNA fragments were identical to S 3 -and S 4 -RNase alleles, which were recently reported by Hanada et al (2014). Of the 113 peach cultivars analyzed, 9, 70, 5, 7, 18, and 4 belonged to S 1 S 1 , S 1 S 2 , S 1 S 3 , S 1 S 4 , S 2 S 2 , and S 2 S 4 genotypes, respectively (Table 1).…”
Section: S-rnase Alleles In Prunus and Malussupporting
confidence: 76%
See 2 more Smart Citations
“…As a result, two out of the four DNA fragments were identical to S 1 -and S 2 -RNase alleles. The remaining two DNA fragments were identical to S 3 -and S 4 -RNase alleles, which were recently reported by Hanada et al (2014). Of the 113 peach cultivars analyzed, 9, 70, 5, 7, 18, and 4 belonged to S 1 S 1 , S 1 S 2 , S 1 S 3 , S 1 S 4 , S 2 S 2 , and S 2 S 4 genotypes, respectively (Table 1).…”
Section: S-rnase Alleles In Prunus and Malussupporting
confidence: 76%
“…Here, two additional alleles, SFB 3 and SFB 4 , have been identified in peach. A more recent study reveals that SFB 3 is only present in ornamental cultivars, while SFB 4 is identified mainly in wild strains (Hanada et al 2014). However, our study indicates that the SFB 3 allele is present in both ornamental cultivar Juhuatao and edible cultivars such as Disertered and Wanpantao, and the SFB 4 allele is present only in cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Peach and almond speciation presumably occurred as the progenitor species expanded its distribution to humid regions of eastern Asia and dry regions of western Asia, respectively. Hanada et al (2014) reported that the S1 haplotype in peach is a pollen part mutant version of the almond Sk haplotype.…”
Section: Idfentification Of Prunus S-rnase Genesmentioning
confidence: 99%
“…When the S-allele haplotype of the pollen is identical to either of the two S-alleles present in diploid pistil, pollen tube growth will be arrested (Pimienta et al 1983;Channuntapipat et al 2001;Kodad et al 2008b) and fertilization prevented. The term 'S-haplotype' is used to describe variants of the S-locus, whereas the term ''S-allele'' is used to describe the variant of a given S-locus gene (Hanada et al 2014). The S-locus encodes a series of glycoproteins known as S-RNases with ribonuclease activities in the style, as well as an F-box gene (SFB) that functions in the pollen (Ushijima et al 2003).…”
mentioning
confidence: 99%